Por todos os meios legítimos e legais: as lutas contra a escravidão e os limites da abolição (Brasil, Grão-Pará: 1850-1888) - Bezerra Neto, José Maia (2009)
Between the decades of 1850 and 1880, in the province of Pará, Empire of Brazil, several antislavery and emancipationist societies were founded. At that time, antislavery societies proclaimed themselves against slavery, not necessarily encompassing an abolitionist or emancipationist thought. Emancipationist societies were characterized by the proposition of a gradual emancipation of slavery, and the recognition of slave owners property rights. From the 1880s onwards, however, several abolitionists groups were founded, which proposed an immediate abolition of slave work, even objecting any property right over the slaves. That does not mean that emancipationist and abolitionist were clearly distinct. On the contrary, this dissertation explores the connections between both trends, even if they represented different solutions for the so called Questão Servil . This dissertation considers both emancipationist and abolitionist societies as a place of political struggle, including different viewpoints and conflicts within these two perspectives, as well as those shared by different groups of free men and slaves. This was because the limit of the abolition of the slavery in Brazil was gradualism, which blurred the distinctions between emancipationists and abolitionist. Moreover, the strength of gradualism as part of a conservative mentality was not restricted to the elites. Therefore, even if on 13 May 1888 slavery was unconditionally abolished and without any financial compensation, abolitionism did not prevail as a wide social reforms program